An individual-subject. The Self as a Complex Unity - Campero, María Belén (Revista de Filosofía, 2017)
The question about the subject involves us in different kinds of problematics that seem irresolvable, however, the subject in his own inquiry about himself can expose and communicate them. The affairs that interpellate the subject clearly refer the individual self but this self is-being in life and is able of self-recognizing in its relation to the world. In this study, following Edgar Morin, we will try to show that the subject is simultaneously con-formed in a web which is both social and individual and that it must be considered in this way to be understood.
Keywords: individuality; dependence; autonomy; identity; organization.